Adhesion State Estimation for Electrostatic Gripper Based on Online Capacitance Measure - Ion-Dan Sîrbu; Marco Bolignari; Salvatore D’Avella; Francesco Damiani; Lorenzo Agostini; Paolo Tripicchio; Rocco Vertechy; Lucio Pancheri; Marco Fontana (Actuators, 2022)
Electroadhesion is a suitable technology for developing grippers for applications where fragile, compliant or variable shape objects need to be grabbed and where a retention action is typically preferred to a compression force. This article presents a self-sensing technique for electroadhesive devices (EAD) based on the capacitance measure. Specifically, we demonstrate that measuring the variation of the capacitance between electrodes of an EAD during the adhesion can provide useful information to automatically detect the successful grip of an object and the possible loss of adhesion during manipulation. To this aim, a dedicated electronic circuit is developed that is able to measure capacitance variations while the high voltage required for the adhesion is activated. A test bench characterization is presented to evaluate the self-sensing of capacitance during different states: (1) the EAD is far away from the object to be grasped; (2) the EAD is in contact with the object, but the voltage is not active (i.e., no adhesion); and (3) the EAD is activated and attached to the object. Correlation between the applied voltage, object material and shape and capacitance is made. The self-sensing EAD is then demonstrated in a closed-loop robotic application that employs a robot manipulator arm to pick and place objects of different kinds.